Comparability of six different immunoassays measuring SARS‐CoV‐2 antibodies with neutralizing antibody levels in convalescent plasma: From utility to prediction. Issue 10 (17th August 2021) - Lamikanra, Abigail; Nguyen, Dung; Simmonds, Peter; Williams, Sarah; Bentley, Emma M.; Rowe, Cathy; Otter, Ashley David; Brooks, Tim; Gilmour, Kimberly; Mai, Annabelle; Dadhra, Jusvinder; Csatari, Mabel; et al.
Abstract: Background: Convalescent plasma (CP) therapy for coronavirus disease (COVID‐19) provides virus‐neutralizing antibodies that may ameliorate the outcome of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infections. The effectiveness of CP likely depends on its antiviral neutralizing potency and is determined using in vitro neutralizing antibody assays. Study design and methods: We evaluated abilities of three immunoassays for anti‐spike antibodies (EUROimmun, Ortho, Roche), a pseudotype‐based neutralization assay, and two assays that quantify ACE2 binding of spike protein (GenScript and hemagglutination test [HAT]‐based assay) to predict neutralizing antibody titers in 113 CP donations. Assay outputs were analyzed through linear regression and calculation of sensitivities and specificities by receiver operator characteristic (ROC) analysis. Results: Median values of plasma samples containing neutralizing antibodies produced conversion factors for assay unitage of ×6.5 (pseudotype), ×19 (GenScript), ×3.4 (HAT assay), ×0.08 (EUROimmun), ×1.64 (Roche), and ×0.10 (Ortho). All selected assays were sufficient in identifying the high titer donations based on ROC analysis; area over curve ranged from 91.7% for HAT and GenScript assay to 95.6% for pseudotype assay. However, their ability to predict the actual neutralizing antibody levels varied substantially as shown by linear regression correlation values (from 0.27 for Ortho to 0.61 for pseudotype assay). Discussion: Overall, the study data demonstrate that all selected assays were effective in identifying donations with high neutralizing antibody levels and are potentially suitable as surrogate assays for donation selection for CP therapy.